Organizational Agility as a Driver of Productivity and Economic Resilience in Emerging Market Economies - Marina Susanti; Lestari Putri (Generasi Sains Indonesia, 2025)
This study investigates the impact of agile management practices on organizational efficiency and employee productivity in emerging economies, focusing on technology, manufacturing, and services sectors. Data were collected from 200 organizations, including responses from 150 managers and 50 employees, and analyzed using a quantitative approach with regression techniques to examine the relationship between agile practices, efficiency, and productivity. The results show that agile practices significantly improve organizational efficiency (β = 0.56, p < 0.01) and employee productivity (β = 0.45, p < 0.01), with technology firms achieving the greatest benefits, manufacturing firms reporting lower adoption and fewer outcomes, and service organizations demonstrating moderate improvements. These findings highlight that while agile management enhances efficiency and productivity overall, its effectiveness varies across sectors, indicating that organizations in emerging economies should adapt agile frameworks to industry-specific conditions to achieve optimal results.